Nano-engineered hydrocolloid-based delivery systems for natural flavonoids: From structural diversity to bioavailability enhancement and therapeutic applications - Yueming Wang; Amin Zhang; Wenjie Chu; Chengliang Qi; Tianxing Zhou; Yu Pan; Yuhan Wang; Chengyang Wang; Yuan Liu; Wenli Wang (Food Hydrocolloids, 2027)

Global drivers and pathways of mariculture maturation, 1997–2022 - Guo Yu; Yueming Liu; Xiaomei Yang; Yonglong Lu; Vincent Lyne; Zhihua Wang (Aquaculture, 2027)

Remote sensing and statistical data integration for spatial discrimination and mapping of mariculture products: A case study of Sansha Bay - Jie Jiang; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Dan Meng; Meiqi Zhou; Jialiang Liu (Ocean & Coastal Management, 2026)

MaHPCA1 alleviates chilling injury in banana fruit - Yu Hou; Peipei Fan; Xiangbin Xu; Zhengke Zhang; Yonggui Pan; Lanhuan Meng; Lisha Zhu; Haiming Chen; Jianbo Xiao; Yueming Jiang; Jiali Yang (Postharvest Biology and Technology, 2026)

Towards low-carbon grain storage buildings: a systematic review of assessment methods and mitigation strategies - Ruoting Liu; Fei Yu; Meng Ouyang; Qi Zhao; Yueming Wen (Energy and Buildings, 2026)

Nitrogen nutrition diagnosis of sweetpotato based on critical nitrogen dilution curve under different water conditions - Xu Zhao; Ximing Xu; Jing Yu; Minghuan Jin; Siyu Wang; Yueming Zhu; Guoquan Lu; Zunfu Lv (Irrigation Science, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Transforming from ‘natural tools’ into ‘custom sensors’: combining directionally designed biological nanopore electrochemistry sensing lumens with AI-driven analytics to pioneer a new paradigm for food analysis - Yanyang Yu; Yongfei Deng; Zhiyong Cui; Yueming Wang; Chenxi Zhang; Jinna Wang; Danni Zhang; Tianxing Zhou; Chuyue Gong; Shengli Zhang (Trends in Food Science & Technology, 2026)

Sealing behavior of bolted flange system with double metallic C-rings during prolonged high-temperature operation - Yijun Chai; Yunzhou Wu; Wenhao Yu; Qin Ma; Xiongwei Yang; Yueming Li (Annals of Nuclear Energy, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

In vitro digestion and faecal fermentation of starch-lipid complexes with distinct crystalline forms prepared by extrusion-cooking - Chen Chao; Rong Sun; Yueming Zhu; Cuiping Wang; Jinglin Yu; Shujun Wang (Carbohydrate Polymers, 2026)

Spatiotemporal heterogeneity of human footprint across China's coastal zone: Integrating geomorphic and policy drivers - Dan Meng; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Ku Gao (Ocean & Coastal Management, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Single-cell dissection of pleural and systemic immunity uncovers pathogen-specific immune reprogramming in tuberculosis versus lung adenocarcinoma - Sifei Yu; Yueming Liang; Jing Chen; Beiying Zhang; Chuling Zhang; Yuwen Zhao; Rong Yan; Yichu Nie; Xiaofan Mao (Inflammation Research, 2026)

Contrasting soil structure and yield responses to 8-year conservation tillage in Fluvo-aquic and Shajiang black soils - Tianyu Ding; Zichun Guo; Yueming Chen; Zizhou Yu; Shenzhong Tian; Jianli Liu; Xinhua Peng (European Journal of Agronomy, 2026)

Montmorillonite-derived Mg-doped NaAlSiO4 for radiative cooling applications - Zhizheng Xiang; Zhongqiu Tong; Haowei Yang; Jie Yu; Yingjun Xiao; Yueming Wang; Shaoyuan Li; Xingang Li; Mikhail M. Mikhailov; Wenhui Ma (Chemical Engineering Journal, 2025)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Astragaloside IV improves the quality of in vitro postovulatory aged oocytes by decreasing oxidative stress in mice - Yueming Wang; Yu Wang; Yashi Fan; Fanglin Xiang; Yuechan Wang; Jinmei Cheng (Theriogenology, 2025)

Transient Power Stabilization in Marine Microgrids: Improved Droop Control and Feedforward Strategies for Heterogeneous Gas Turbines with Hybrid Energy Storage - Zemin Ding; Yueming Li; Yongbao Liu; Youhong Yu (Journal of Marine Science and Engineering, 2025)
To address the complexity of power allocation in parallel operation systems combining single-shaft and split-shaft gas turbine generators, this paper proposes a coordinated power allocation strategy based on enhanced voltage droop control for marine power systems integrated with hybrid energy storage comprising flywheel and battery subsystems. Furthermore, to mitigate significant power sharing deviations during transient/pulsed load conditions in shipboard application, a feedforward compensation strategy is developed. Simulation results demonstrate that the improved droop control maintains power sharing deviations below 3.5% across steady-state operations and gradual load variations, ensuring system stability and balanced power distribution. However, abrupt load changes induce over 20% deviations, compromising parallel operation reliability. The proposed feedforward compensation strategy effectively restricts deviations within 4% under specified transient and pulsed load scenarios, satisfying both parallel operation criteria and grid power quality requirements. Validation is performed on a parallel system comprising two distinct gas turbine configurations.

Mapping of Rsn2, a locus conferring rice tolerance to toxin from the causal agent of rice sheath blight Rhizoctonia solani - Xiang Xue; Yu Wang; Yueming Xu; Yumei Zhang; Fang Gu; Yuyin Ma; Zongxiang Chen; Yafang Zhang (Journal of Plant Pathology, 2025)

Mitigating particulate matter dispersion from urban earthen sites: A case study of city walls in Zhengzhou, China - Yueming Wen; Yu Miao; Renjing Zhao; Yaowen Shi; Jiangxing Miao; Chang Lv; Guang Zhang (Sustainable Cities and Society, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Identification of novel natural anti-browning agents based on phenotypic and metabolites differences in potato cultivars - Yueming Tang; Yiwen Yang; Fangyao Luo; Jinghong Luo; Jianjun Hu; Haoqiang Yu; Wanchen Li; Jia Gao; Fengling Fu (Food Chemistry, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Tert-Butylhydroquinone retards longan fruit deterioration by regulating membrane lipid and energy metabolisms - Zhiqian Yu; Dingtao Tang; Zhengke Zhang; Yueming Jiang; Jiali Yang; Yonggui Pan (Food Chemistry, 2024)

Lithology and elevated temperature impact phoD-harboring bacteria on soil available P enhancing in subtropical forests - Fujing Pan; Qian Yang; Yueming Liang; Xuan Yu; Peilei Hu; Wei Zhang; Yuelan Pang (Science of The Total Environment, 2024)

Application of multilevel immobilized carbon nanotube/sulfur doped carbon nitride composite photocatalytic coating for Cr6+(aq.) reduction - Zhenyu Shi; Lei Rao; Peifang Wang; Yueming Yu (Chemical Engineering Journal, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Evaluation of coastal zone development and utilization considering natural ontology, a case study in Liaoning Province, China - Guo Yu; Zhihua Wang; Yueming Liu; Xiaomei Yang; Junyao Zhang; Ku Gao (Ocean & Coastal Management, 2024)

Vegetation recovery reshapes the composition and enhances the network connectivity of phoD-harboring microorganisms to promote P availability in a karst ecosystem - Fujing Pan; Xuan Yu; Min Chen; Yueming Liang (Science of The Total Environment, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Liraglutide attenuates palmitate-induced apoptosis via PKA/β-catenin/Bcl-2/Bax pathway in MC3T3-E1 cells - Lanlan Cheng; Yijing Xu; Yueming Long; Fangmei Yu; Li Gui; Qiu Zhang; Yunxia Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Hypergolic ignition induced by head-on collision of bi-propellant droplets: Monoethanolamine-based fuel and hydrogen peroxide - Dawei Zhang; Dehai Yu; Yueming Yuan; Peng Zhang; Xuejun Fan (Fuel, 2023)

Heat transfer behavior of an immersed tube with sCO2 working fluid in a hot fluidized bed at high pressure - Yu Huang; Xu Bao; Yuanqiang Duan; Lin Li; Dongdong Fang; Yueming Wang; Lunbo Duan (Fuel, 2023)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Experimental study on full-scale steel beam-to-column moment connections - Jiaru Qian; Haiqun Yu; Feng Yan; Hai Dong; Jianhua Li; Yueming Liu (Earthquake Engineering and Engineering Vibration, 2005)

Characterization of seed hordeins and varietal identification in three barley species by high-performance capillary electrophoresis - Yueming Yan; Yi Jiang; Jianzhong Yu; Minhua Cai; Yingkao Hu; Dragan Perovic (Cereal Research Communications, 2003)

Allelic variation of the HMW glutenin subunits in Aegilops tauschii accessions detected by sodium dodecyl sulphate (SDS-PAGE), acid polyacrylamide gel (A-PAGE) and capillary electrophoresis - Yueming Yan; S.L.K. Hsam; Jianzhong Yu; Yi Jiang; F.J. Zeller (Euphytica, 2003)